Potencial antimicrobiano e antibiofilme do óleo essencial de folhas de Croton blanchetianus Baill. sobre microrganismos de interesse clínico - Malveira, Ellen Araújo (2023)
The inappropriate use of antibiotics favors the acquisition of resistance by microorganisms, and is considered a serious recurring public health problem, which can cause morbidity and mortality among patients. The formation of biofilms is one of the factors of microorganism resistance and may be associated with biotic and abiotic factors. Therefore, the search for new bioactive molecules that minimize such problems is important. Natural products, such as essential oils (EOs), have gained prominence as sources of new antimicrobial agents. This study aimed to evaluate the chemical composition, toxicity, and the antimicrobial and antibiofilm potential of EOs extracted from Croton blanchetianus Baill. leaves, as well as their mechanisms of action on microorganisms of clinical interest. GC/MS analysis revealed the presence of major compounds such as spatulenol (20.03%); bicyclogermacrene (5.92%); caryophyllene oxide (5.81); eucalyptol (5.62%). The oil at the concentration of 50 μg mL1 was able to inhibit the planktonic growth of Candida albicans and C. parapsilosis by 78.55 and 75.94%, respectively. There was also inhibition in biofilm formation of C. albicans and C. parapsilosis under oil action with 44.12 and 74.13%, respectively. There was no satisfactory inhibition under oil action against bacteria, Cryptococcus neoformans, Candida krusei and Candida tropicalis. Fluorescence microscopy analyses detected the overproduction of reactive oxygen species (ROS), the formation of pores in the cell membrane and programmed cell death in the yeasts. Scanning electron microscopy analysis showed that treatment with the EO caused damage to morphology in C. albicans and C. parapsilosis. Furthermore, it was evaluated that the oil is not toxic to type A, B and O+ erythrocytes. Thus, C. blanchetianus oil has antifungal and antibiofilm potential against infections caused by C. albicans and C. parapsilosis.